Search for a fermiophobic Higgs boson in $pp$ collisions at $\sqrt{s}=7$ TeV - CMS collaboration (2187 authors) (2012)
Combined results are reported from searches for a fermiophobic Higgs boson in the gamma-gamma, WW, and ZZ decay modes in proton-proton collisions at sqrt(s) = 7 TeV. The explored Higgs boson mass range is 110-300 GeV. The data sample corresponds to an integrated luminosity of 4.9-5.1 inverse femtobarns. A fermiophobic Higgs boson is excluded at 95% confidence level in the mass range 110-194 GeV, and at 99% confidence level in the mass ranges 110-124.5 GeV, 127-147.5 GeV, and 155-180 GeV.